2008
DOI: 10.1364/ao.47.006796
|View full text |Cite
|
Sign up to set email alerts
|

Cross calibration of ocean-color bands from Moderate Resolution Imaging Spectroradiometer on Terra platform

Abstract: Ocean-color applications require maximum uncertainties in blue-wavelength water-leaving radiances in oligotrophic ocean of approximately 5%. Water-leaving radiances from Moderate Resolution Imaging Spectroradiometer (MODIS) on the Terra satellite, however, exhibit temporal drift of the order of 15% as well as sensor changes in response versus scan and polarization sensitivity, which cannot be tracked by onboard calibrators. This paper introduces an instrument characterization approach that uses Earth-view data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 40 publications
0
75
0
Order By: Relevance
“…To limit the data set for the 500 m channels (20 detectors), the M coefficients are generated for the neighboring detector pairs, in other words, at 1 km resolution. For the near-nadir geometries, where azimuthal angle changes rapidly, one should also consider rotation angle α, which is the angle between the sensor reference (scan) plane, with respect to which the Mueller matrix is defined, and plane of observation, defined by the normal to the surface and view direction, with respect to which the Q and U components are calculated (for detail, see Meister et al, 2012;Kwiatkowska et al, 2008;Gordon et al, 1997). Once PC coefficients are produced, Eq.…”
Section: Polarization Correction Of Modis Terra Datamentioning
confidence: 99%
See 1 more Smart Citation
“…To limit the data set for the 500 m channels (20 detectors), the M coefficients are generated for the neighboring detector pairs, in other words, at 1 km resolution. For the near-nadir geometries, where azimuthal angle changes rapidly, one should also consider rotation angle α, which is the angle between the sensor reference (scan) plane, with respect to which the Mueller matrix is defined, and plane of observation, defined by the normal to the surface and view direction, with respect to which the Q and U components are calculated (for detail, see Meister et al, 2012;Kwiatkowska et al, 2008;Gordon et al, 1997). Once PC coefficients are produced, Eq.…”
Section: Polarization Correction Of Modis Terra Datamentioning
confidence: 99%
“…This discipline is very sensitive to the sensor calibration and its temporal changes because the signal used in biomonitoring of the world ocean ("ocean color") is small. The significant temporal drifts of the MODIS Terra ocean color record from the more stable MODIS Aqua and, particularly, the benchmark SeaWiFS (Sea-viewing Wide Fieldof-view Sensor) record were documented in Kwiatkowska et al (2008). These studies also showed that the calibration degradation effect is largest in the shortwave spectrum and rapidly decreases with wavelength.…”
mentioning
confidence: 94%
“…This led to a long-term drift in calibration, most pronounced on the Terra sensor, with the largest in the blue band (B3), and decreasing with increasing wavelength (Xiong and Barnes, 2006). The discovery of systemic nonphysical trends in MODIS Terra products by science users (e.g., Kwiatkowska et al, 2008;Levy et al, 2010;Wang et al, 2012) motivated research into independent trend characterization for C6 calibration. Analysis of observations of remote desert targets that were assumed to be nearly invariant over the long term were used to constrain the long-term drift of the observations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, any changes to instrument behavior on-orbit, or deviation from prelaunch understanding of known anomalies, would require either new corrections or modification to existing ones. For heritage instruments, this process can require a lengthy time series, as was the experience with MODIS, on the EOS satellites Aqua 5 and Terra, 6 in determining the polarization response on-orbit. To produce a consistent data record, any new or revised correction will need to be applied retrospectively.…”
Section: Processing Systemmentioning
confidence: 99%
“…However, if the degradation measured by the SDSM is large, it is likely that the SD reflectance for the VIIRS telescope view angle is significantly different. These effects could be responsible for the corrections that need to be applied to the MODIS Terra SD measurements 6 . In that case, the MODIS Terra SD door became stuck open due to a mechanism malfunction in May 2003, leading to a large increase in the rate of degradation of the SD reflectance; both the SD reflectance degradation and the required corrections are largest at 412nm.…”
Section: Solar Diffuser Reflectance Degradationmentioning
confidence: 99%